Preparation of eye balls of rat and mice for histopathological examination in toxicological-studies - JANARDHAN, K S; NIRODY, GEETA; BALAJI, M R; KAMALA, K (The Indian Journal of Animal Sciences, 2014)
A study was conducted to standardize the procedure for preparation of eye balls of rats and mice, for histopathologicalevaluation in toxicological studies, using 10% n-eutral buffered formalin and Davidson's fluid. Davidson's fluid proved to . I be a good fixative, but prolonged' fixation in 'the same, hardened the lenses. Formalin fixation hardened the lenses to a greater extent and thus resulted in artefactual changes. Better results were obtained with chloroform, as a clearing agent, when compared to xylene. More than 95% results were attained with shorter duration of fixation in Davidson's fluid, along with use of chloroform as a clearing agent during processing.